PERANCANGAN SISTEM PENUNJANG KEPUTUSAN PENILAIAN KINERJA PEGAWAI STAFF PADA PT. CIPTABANGUN NUSANTARA BERBASIS WEB - Sigit Apri, - (2018)
This study aims to make Application of Employee Performance Evaluation Information System at PT. Cipta Bangun Nusantara based web. This is because at this time PT. Cipta Bangun Nusantara still performs the data recapitulation using Microsoft Excel on routine employee performance reporting activities conducted every month, which will determine the rewards received by employees in accordance with the reporting performance recapitulated for 6 months. The method used in this research is waterfall where the calculation using WP (Weighted Product) method. Analysis method used is PIECES (Performance, Information, Economic, Control, Efficiency, Service). After PIECES analysis, we need a language to describe a system using UML as well as web-based programming application, PHP. The scope of this system includes the data value of employees who will be processed into an information in the form of rewards employees will receive a contract extension or not by using the SPK method, the user of this system are employees, admin, staff operational staff and Manager. The results of this study is to design an employee information assessment system that can facilitate the company in the process of reporting, data recapitulation, and employee performance appraisal at PT. Cipta Bangun Nusantara so that the reporting process, data recapitulation, and employee performance appraisal are more effective and efficient